A Review Article on Home Environment, Examination Anxiety, And Academic Achievement of Higher Secondary Students - .K, Sindhu; S, Poonguzhali. (Journal of Neonatal Surgery, 2025)
Academic achievement holds significant importance not only for the student but also for those around them. It is widely recognized that academic success is influenced by two broad categories of factors: subjective (individual) factors and objective (environmental) factors. Subjective factors relate to the personal attributes of the individual, while objective factors are associated with the individual's environment. Emotional maturity is one of the key individual, non-cognitive factors that may impact a student's academic achievement. In a study investigating the effects of home environment and academic achievement on mental health, a sample of 300 secondary school students was examined, comprising 150 female and 150 male participants. The results revealed that the mean mental health score for girls was 74.7, while for boys it was 70. These findings indicate that, on average, girls demonstrated better mental health compared to boys